2011
DOI: 10.1007/s12032-011-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of human papillomavirus sequences in epithelial breast cancer in a Mexican female population

Abstract: The role of human papillomavirus (HPV) in breast cancer is controversial. We evaluated 118 breast carcinomas and two paraffin-embedded tissues of lesions of the nipple of Mexican patients for HPV sequences. No carcinoma sample exhibited koilocytosis, in contrast to lesions of the nipple. We subjected purified DNAs to PCR employing two HPV16/E6 or GP5/6 primer set oligonucleotides. Results showed that HPV DNA sequences were absent in the breast tissues. Absence of HPV in breast carcinoma failed to support an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
8
0
3
Order By: Relevance
“…Therefore, our results, which can represent the basis for future studies, should be carefully evaluated because only a few HPV positive cases were identified and other studies found HPV in breast tissues with estrogen-receptor expression [ 24 ]. Moreover, the low viral load, detected in several studies [ 25 , 26 ], can explain the low frequency of HPV-positive series.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our results, which can represent the basis for future studies, should be carefully evaluated because only a few HPV positive cases were identified and other studies found HPV in breast tissues with estrogen-receptor expression [ 24 ]. Moreover, the low viral load, detected in several studies [ 25 , 26 ], can explain the low frequency of HPV-positive series.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published studies do not follow a precise methodology, and the screening criteria used are very heterogeneous. Some studies only consider juvenile malignancies [34], while others include inflammatory breast cancer tissues [48, 49], triple-negative tumors [50], medullary malignancies [51], metaplastic breast cancer [52], papillary lesions [20, 53], Paget’s disease [54], or carcinoma in situ [9, 24, 25, 36, 41, 55–60]. In addition, no standards are used in selecting the molecular technique to screen for viruses, implying the potential detection of different viral serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While these data indicate that HPVs may have a possible role in some breast cancers, they may not have a major causal role. There are two reasons for this view: (i) in immunocompromised patients (due to either human immunodeficiency infections or post organ transplantation therapy), there is no increased prevalence of breast cancer, which is in contrast to the two- to sixfold increased prevalence of HPV associated cervical and head and neck cancer in these patients ( 10 ), and (ii) the HPV viral load in breast cancer is extremely low ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%